Mobile sensing system for georeferenced performance monitoring in cycling - Oliveira, Diogo S. (2015)
In recent years there has been a significant evolution regarding applications for mobile devices that provide location-based services. The mobile devices available on the market already provide a set of integrated sensors and it is also possible to acquire data from external sensors. This paper presents the development and results concerning a mobile sensing system applied to cycling which performs data collection using both sensors integrated in the smartphone and multiple wireless sensor nodes, which are used to acquire relevant performance parameters. The data collected by the developed mobile app is stored in a local database and also uploaded to a remote database, where it can be accessed later using the mobile app or a web browser. This mobile app allows users to share data with friends, join or create events, locate friends, consult graphs and access past routes in a map. Based on these functionalities, this system aims to provide detailed feedback regarding the user performance and enhance the enjoyment of the cyclists.